Predictors of nonresponse to treatment and low adherence to internet-based cognitive behavioral therapy in depressed/anxious women facing the couple’s fertility problems: a secondary analysis of a randomized control trial - Shiva Shafierizi; Zahra Basirat; Fatemeh Nasiri-Amiri; Farzan Kheirkhah; Zahra Geraili; Hajar Pasha; Mahbobeh Faramarzi (BMC Psychiatry, 2024)
Abstract Background The study aimed to examine the predictors of treatment nonresponse and low adherence to Internet-based cognitive behavioral therapy and face-to-face therapy for treating depression and anxiety in women facing the couple’s fertility problems. Methods This is a secondary analysis based on a previous randomized controlled trial including 152 depressed/anxious women facing the couple’s fertility problems. The study defines low adherence as receiving less than 4 sessions (out of 8 sessions). Nonresponse to treatment refers to a < 50% reduction in the anxiety and depression total scores. Results A high level of anxiety/depression score before psychotherapy increases the risk of nonresponse to both Internet-based and face-to-face psychotherapies by 1.4 to 2 times in women facing the couple’s fertility problems after the treatment and in the 6-month follow-up. However, 4 factors, including diagnosis of mixed anxiety and depression, low education level, long marriage duration, and infertility caused by mixed female/male factors, reduced the risk of nonresponse to psychotherapies. Conclusion Women facing the couple’s fertility problems with high depression and anxiety scores are at risk of poor prognosis in response to psychotherapy. Psychologists and healthcare providers of infertility centers should pay more attention to the timely identification and referral of depressed/anxious patients to psychologists.